Defense mechanisms and inflammatory bowel diseases: a narrative review - Orlando Silvestro; Carmelo M. Vicario; Ludovico Costa; Giorgio Sparacino; Trine Lund-Jacobsen; Chiara A. M. Spatola; Emanuele M. Merlo; Anna Viola; Concetto M. Giorgianni; Antonino Catalano; Walter Fries; Gianluca Lo Coco; et al. (Research in Psychotherapy)
Growing evidence highlights the crucial role of defense mechanisms in the context of chronic diseases. However, few studies have evaluated the impact of these implicit emotion regulation strategies on the adaptation processes related to inflammatory bowel diseases (IBD). This narrative review aimed to explore the role of defense mechanisms in patients with IBD and clarify their association with related psychological and physical symptoms. A literature search was conducted using PubMed and PsycINFO databases to select studies considering defense mechanisms in patients with IBD. Inclusion criteria were English language articles, diagnosis of Crohn’s disease or ulcerative colitis, and use of validated assessment instruments specifically related to defense mechanisms. Six studies, including a total of 664 patients, were deemed eligible. Immature defense mechanisms were commonly detected in IBD patients, with significant effects on psychological and physical health. Significant associations were found between defense mechanisms, perceived health-related quality of life (HR-QoL), and psychological distress. Findings suggested that immature defense mechanisms may negatively impact the management of disease, leading to lower perceived HR-QoL, decreased treatment adherence, and increased risk of psychopathological symptoms. Considering these findings, we suggest that an integrated clinical evaluation, including an in-depth investigation of defense mechanisms, may promote more effective psychological treatments and improve psychological well-being in patients suffering from IBD.